Evaluating the impact of a time orientation intervention on well-being during the COVID-19 lockdown: past, present or future?. Issue 3 (4th May 2022) - Dennis, Amelia; Ogden, Jane; Hepper, Erica G.
ABSTRACT: Lockdown policies brought on by the COVID-19 pandemic pose a threat to well-being. This study examined the effectiveness of three positive psychology interventions, with different time-orientations, on well-being as well as predictors of well-being during lockdown. Participants ( n = 261) completed measures of lockdown characteristics, attachment orientation, and emotion regulation, were then randomly allocated to one of four interventions; nostalgia (past), gratitude (present), best possible self (BPS; future) or control (recalling a TV show), and completed outcome measures of well-being and affect. Results showed that BPS resulted in higher positive affect and that both BPS and gratitude resulted in higher social connectedness than the nostalgia intervention. Further, greater well-being during lockdown was predicted by greater attachment security, greater emotion regulation, and more social interactions. In sum, focusing on the present or future during lockdown is more effective for well-being than focusing on the past, which alongside trait characteristics predict well-being under lockdown.